1998
DOI: 10.1159/000056413
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Tumors and Gamma Knife Surgery - Clinical Experience with More Than Two Years of Follow-Up

Abstract: 30 patients with pituitary tumors were treated in our unit and followed for 26–45 months. 14 patients had nonsecreting adenomas, 7 had acromegaly, 5 had prolactinomas, 3 had Cushing''s disease. One patient had a choristoma of the pituitary stalk. The patient with a choristoma, 7 patients with nonsecreting adenomas, 4 with acromegaly, 1 prolactinoma and 3 with Cushing’s disease had been operated by transsphenoidal microsurgery prior to Gamma Knife (GK) treatment. From this group, one patient with a nonsecreting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 11 publications
1
33
0
4
Order By: Relevance
“…Therefore, additional therapy after operation is often necessary. For such cases, conventional external radiation has been known to be effective, but it takes several years to achieve endocrinological remission and also carries a significant risk for panhypopituitarism or visual disturbances 20,25,26) . Radiosurgery can be a first choice of treatment, achieving both growth control and hormonal remission with minimum neurological complications, which is equivalent to conventional radiation therapy but with much less risk of radiation injury to the surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional therapy after operation is often necessary. For such cases, conventional external radiation has been known to be effective, but it takes several years to achieve endocrinological remission and also carries a significant risk for panhypopituitarism or visual disturbances 20,25,26) . Radiosurgery can be a first choice of treatment, achieving both growth control and hormonal remission with minimum neurological complications, which is equivalent to conventional radiation therapy but with much less risk of radiation injury to the surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
“…Witt et al 51 reviewed 20 different radiosurgery studies published between 1997 and 2002 and found that tumor control ranged from 68 to 100% (but most studies showed Ͼ 90% growth control). He also found endocrine improvement in 0 16,29,53,54 to 67%, 35 depending on the study. The endocrine cure in the different studies ranged from 0 16,36 to 96%.…”
Section: Acromegalymentioning
confidence: 91%
“…In a review of 17 different radiosurgery studies published from 1997 to 2002, Witt 50 found that endocrine improvement was achieved with radiosurgery in 29 43 to 100% 29,36 of cases. Tumor control is achieved in most studies in Ͼ 90% of cases, 29,36,43,54 with the exception of 1 study in which only a 68% growth control rate was reported. 16 Cure after radiosurgery was difficult to assess because persistent mild hypersecretion of prolactin may have developed in many patients due to the radiation-induced destruction of the stalk, and therefore to the inhibitory effect of dopaminergic neurons.…”
Section: Prolactin-secreting Adenomasmentioning
confidence: 97%
“…Os dados com a radiocirurgia gamma-knife -que permite liberar, com acurácia milimétrica e de uma só vez, dosess maiores de radiação para o núcleo do tumor, com menor agressão sobre o hipotálamo, quiasma óptico e cérebro -são ainda limitados (69). Em três estudos, totalizando 16 pacientes, não houve normalização dos níveis de PRL, mas redução dos mesmos aconteceu na maioria dos casos (69)(70)(71). A radioterapia deve ser reservada para prolactinomas (sobretudo, os invasivos) sem resposta adequada às outras formas de tratamento (16).…”
Section: Radioterapiaunclassified